A high performance trench gate tunneling field effect transistor based on quasi-broken gap energy band alignment heterojunction. (28th May 2022) - Chen, Shupeng; Wang, Shulong; Liu, Hongxia; Han, Tao; Zhang, Hao
Abstract: In this letter, a tunneling field effect transistor based on quasi-broken gap energy band alignment (QB-TFET) is proposed and investigated by simulation method. To offering high on-state current, InGaAs/GaAsSb heterojunction with quasi-broken gap energy band alignment is applied to QB-TFET to improve the band-to-band tunneling rate. Trench gate structure and InGaAs pocket layer are applied to further increase the tunneling efficiency. To suppress the leakage current caused by the off-state tunneling path from source to drain, an intrinsic InGaAs spacer is inserted between n+ InGaAs drain and p+ GaAsSb source. In order to further improve the control ability of gate voltage on channel, TiO2 is used as the gate dielectric of the proposed QB-TFET. Moreover, the effect of x and y fraction of In x Ga1– x As and GaAs y Sb1– y on quasi-broken gap tunneling junction are studied in this work. The electrical characteristic change of QB-TFET with different x and y fraction is analyzed. The proposed QB-TFET is compared with other works and shows an obvious advantage on performance. As a result, a large on-state current ( I on ) of 921 μ A μ m −1 can be obtained. Moreover, steep average subthreshold swing (SSavg ) of 4.9 mV/dec can be achieved when I on  = 1 μ A μ m −1 .